Related Party Transactions and Tax Avoidance: Study on Mining Company in Indonesia - Rezeki, Dwi Sri; Widarjo, Wahyu; Sudaryono, Eko Arief; Syafiqurrahman, Muhammad (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2021)
This study aims to provide empirical evidence of the effect of related party transactions on tax avoidance on mining sector companies listed in the Indonesia Stock Exchange. The research sample consists of 73 observations. We used Discretionary Permanent Book Tax Differences to measure the ratio of tax avoidance and used the composite value of the merging of sales, purchase, liability and receivable to related party through principal component analysis to measure related party transactions variables. The results of panel regression analysis show that related party transactions has a positive and significant effect on Discretionary Permanent Book Tax Differences. These results are consistent after re-testing by using a variable measurement of different tax avoidance, namely the Cash Effective Tax Rate. Furthermore, the results of the analysis per component of related party transactions show that only receivable transactions have a significant effect on tax avoidance. This study results indicate that in the taxation context, company policy in related party transactions is not conducted partially per component. Company management is likely to use all of the related party transactions methods so that the tax avoidance practices are not easily detected by stakeholders, particularly revenue officers.